2017
DOI: 10.1038/bjc.2017.77
|View full text |Cite
|
Sign up to set email alerts
|

LDL cholesterol counteracts the antitumour effect of tyrosine kinase inhibitors against renal cell carcinoma

Abstract: Background:Treatment with tyrosine kinase inhibitors (TKIs) significantly improves survival of patients with renal cell carcinoma (RCC). However, about one-quarter of the RCC patients are primarily refractory to treatment with TKIs.Methods:We examined viability of RCC and endothelial cells treated with low-density lipoprotein (LDL) and/or TKIs. Next, we validated the potential role of PI3K/AKT signalling in LDL-mediated TKI resistance. Finally, we examined the effect of a high-fat/high-cholesterol diet on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Cell lines, once plated, were cultured no longer than 3 weeks. The patient-derived PNX0010 clear cell renal cell carcinoma (ccRCC) cell line was described previously (25). hTERT-RPE1 cells were cultured in DMEM/F-12 medium (Life Technologies) supplemented with 10% FBS plus 1Â penicillin/streptomycin, 1Â Glutamax-I (Gibco/Thermo Fisher Scientific), and 0.01 mg/mL hygromycin B (Life Technologies).…”
Section: Cell Culture Cell Lines and Plasmidsmentioning
confidence: 99%
“…Cell lines, once plated, were cultured no longer than 3 weeks. The patient-derived PNX0010 clear cell renal cell carcinoma (ccRCC) cell line was described previously (25). hTERT-RPE1 cells were cultured in DMEM/F-12 medium (Life Technologies) supplemented with 10% FBS plus 1Â penicillin/streptomycin, 1Â Glutamax-I (Gibco/Thermo Fisher Scientific), and 0.01 mg/mL hygromycin B (Life Technologies).…”
Section: Cell Culture Cell Lines and Plasmidsmentioning
confidence: 99%
“…In RCC cell line studies, inhibition of mTORC1 suppressed tumor growth, cell survival, angiogenesis, and metastasis (10,11). Furthermore, our previous studies demonstrated that activation of the PI3K/Akt/mTORC1 pathway enhanced resistance to VEGF-targeted agents in RCC cell lines (12,13). Resistance to the VEGF-targeted agent sunitinib is correlated with phosphatase and tensin homolog deleted from chromosome 10 (PTEN) expression, and restoration of PTEN expression restores sensitivity to sunitinib (12).…”
Section: Introductionmentioning
confidence: 95%
“…Resistance to the VEGF-targeted agent sunitinib is correlated with phosphatase and tensin homolog deleted from chromosome 10 (PTEN) expression, and restoration of PTEN expression restores sensitivity to sunitinib (12). Akt activation by low-density lipoprotein (LDL) addition in RCC cell lines counteracts the anti-tumor effects of the VEGF-targeted agents sunitinib and sorafenib (13). In adition, we have previously reported that high levels of 4EBP1/eIF4E activeation predict higher recurrence rate (14).…”
Section: Introductionmentioning
confidence: 99%
“…In the present in vivo study, development of hypercholesterolemic phenotype impelled us to investigate the effect of elevated lipid parameters on the efficacy of sorafenib in HCC cells. To mimic hypercholesterolemic condition in vitro, cells were provided with LDL cholesterol exogenously and evaluated for the response to sorafenib [ 43 ]. Based on initial screening experiments and literature, sorafenib (5 μM) and LDLc (100 μg/ml) concentrations were selected for HepG2 and HuH-7 cells (Additional file 7 : Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of RAF/MEK/ERK pathway has been linked to the anti-proliferative action of sorafenib [ 11 ]. Additionally, LDLc has been shown to activate ERK by promoting phosphorylation of its upstream activators like Raf and MEK [ 43 46 ]. Thus, to understand whether LDLc decreases toxicity of sorafenib by interfering with signaling pathways, activation of ERK was checked.…”
Section: Resultsmentioning
confidence: 99%